PENGARUH METODE DISCOVERY LEARNING TERHADAP KETERAMPILAN KEAKTIFAN MATEMATIS SISWA - Registiani Awaliyah; Dewi Surani; Ratu Milawati (LPPM Universitas Bina Bangsa, 2023)
This research is motivated by the low activity of students in learning. Based on the results of the study it is known that students experience active learning difficulties in class. The purpose of this study is to realize whether the discovery learning model has an impact on the mathematical activeness of class X students. This research is descriptive quantitative research that is experimental in nature. This observation included class X students of SMK Negeri 1 Serang City for the 2022/2023 academic year, even semester, which consisted of 2 classes with a total of 73 students. In this study, the reviewers were able to take a sample of 35 students as an experimental class and a sample of 38 students as a conventional class. This study uses a questionnaire or questionnaire. The data accumulation technique used a questionnaire test or a math activity test in the form of fifteen statements. This data analysis technique uses a descriptive statistical analysis test, namely an analysis that provides a general description of the characteristics of each research variable as seen from the average, maximum and minimum values. Based on the results of observations, it can be concluded that the results of statistical data show that all indicators in the discovery learning model can be categorized as